High Mobility 3D Dirac Semimetal (Cd3As2) for Ultrafast Photoactive Terahertz Photonics. (23rd February 2021) - Dai, Zijie; Manjappa, Manukumara; Yang, Yunkun; Tan, Thomas Cai Wei; Qiang, Bo; Han, Song; Wong, Liang Jie; Xiu, Faxian; Liu, Weiwei; Singh, Ranjan
Abstract: The Dirac semimetal cadmium arsenide (Cd3 As2 ), a 3D electronic analog of graphene, has sparked renewed research interests for its novel topological phases and excellent optoelectronic properties. The gapless nature of its 3D electronic band facilitates strong optical nonlinearity and supports Dirac plasmons that are of particular interest to realize high‐performance electronic and photonic devices at terahertz (1 THz = 4.1 meV) frequencies, where the performance of most dynamic materials are limited by the tradeoff between power‐efficiency and switching speed. Here, all‐optical, low‐power, ultrafast broadband modulation of terahertz waves using an ultrathin film (100 nm, λ/3000) of Cd3 As2 are experimentally demonstrated through active tailoring of the photoconductivity. The measurements reveal the photosensitive metallic behavior of Cd3 As2 with high terahertz electron mobility of 7200 cm 2 (Vs) −1 . In addition, optical fluence dependent ultrafast charge carrier relaxation (15.5 ps), terahertz mobility, and long momentum scattering time (157 fs) comparable to superconductors that invoke kinetic inductance at terahertz frequencies are demonstrated. These remarkable properties of 3D Dirac topological semimetal envision a new class of power‐efficient, high speed, compact, tunable electronic, and photonic devices. Abstract : Cadmium arsenide (Cd3 As2 ), a 3D Dirac semimetal, exhibits remarkable properties suitable for developing efficient opto‐electronics and photonic devices. Here, using transient THz spectroscopy, long scattering times, high mobility, and phototunable plasmonic properties in Cd3 As2 are shown. An ultrasensitive and ultrafast THz modulator using ultrathin Cd3 As2 is further demonstrated that can enable a novel material platform for compact high‐frequency RF electronics and ultrafast photonics.